Sexually transmitted infections based on the syndromic approach in Gondar town, northwest Ethiopia: a retrospective study - Moges Beyene; Yismaw Gizachew; Kassu Afework; Megabiaw Berihun; Alemu Shitaye; Amare Bemnet; Muluye Dagnachew (BMC, 2013)
Abstract Background Sexually transmitted infections are among the most common causes of illnesses in the world and have far reaching health, social and economic consequences. They are important because of their magnitude, potential complications and interactions with HIV/AIDS. Though the problem may be generally similar to other developing countries, there is scarce information on the incidence and prevalence of sexually transmitted infections in Ethiopia. This study was then aimed to determine the magnitude of sexually transmitted infections among patients visiting a clinic in Gondar town, Northwest Ethiopia. Methods Medical records of patients who visited the clinic from January 2011 to December 2011 were reviewed. Sociodemographic and clinical data were extracted using data extraction form. The data were entered and analyzed using SPSS version 16 statistical package. Descriptive statistics and Chi-square tests were carried out. Results A total of 1071 clients visited the clinic during the study period. Among these, 383 (35.8%) had complained symptoms of sexually transmitted infections. The mean (SD) age of the patients was 26.8 ± 7.4 years. The commonest chief complaints were vaginal discharge (38.4%) and urethral discharge (13.6%). Seventy seven percent of the cases did not bring their sexual partners for treatment. Conclusion There was a high magnitude of STIs in the clinic according to the syndromic approach. However, the actual prevalence of STIs and the associated factors in the community need to be determined through further studies. The results of this study also urge the need for evaluation of the syndromic approach and test for antimicrobial resistance.